Research on Semi-automatic Bomb Fetching for an EOD Robot - Qian Jun; Weng Xin-Hua; Yang Ru-Qing; Zhang Wei-Jun; Zeng Jian-Jun (International Journal of Advanced Robotic Systems, 2008)
An EOD robot system, SUPER-PLUS, which has a novel semi-automatic bomb fetching function is presented in this paper. With limited support of human, SUPER-PLUS scans the cluttered environment with a wrist-mounted laser distance sensor and plans the manipulator a collision free path to fetch the bomb. The model construction of manipulator, bomb and environment, C-space map, path planning and the operation procedure are introduced in detail. The semi-automatic bomb fetching function has greatly improved the operation performance of EOD robot.